Sistemas baseados em cartão: revisão da literatura de novos sistemas e proposta de uma lista de fatores soft para a implementação desses sistemas - Bagni, Gustavo (2019)
Although Production Control Systems are considered a mature topic in literature, up to now, the focus of literature has been on optimizing the operating parameters of each system, assigning little importance to factors related to human influence (soft factors). Implementation, however, remains a complex problem. This paper aims to reduce this gap by proposing, through a combination of research methods, a list of soft factors critical to success in implementing card-based systems, which which are the most studied and implemented and which share as a characteristic a strong human influence on their functioning. However, to achieve this goal, it was initially necessary to identify which systems are based on cards. Although for systems such as Kanban and CONWIP there is a large literature available, systems developed after POLCA proposal in 1998 were little explored. Therefore, this dissertation initially performs a systematic literature review identifying 13 systems developed between 1999 and 2018, such as COBACABANA, DDMRP, Redutex, B-CONWIP, BK-CONWIP, among others. Briefly, it presents how each system works, its characteristics, current research stage and environments in which it has been proved to be useful, aiming to increase researches about them. The systems are also compared in relation to six variables defined in the literature, identifying that many of the new systems are card-based. The soft factors proposed for the implementation of card-based systems are based on the analysis of problems cited in the literature as well as difficulties identified through a longitudinal case study. This list was validated by experts as well as a group of employees from the focus company that participated in the implementation of kanban. This dissertation also proposes a soft factor house for the implementation of card-based systems, in which the factors are classified as exclusive to this theme or classic management factors, as well as in relation to the organizational level in which it operates (organization, implementation group, or individual). This house aims to assist managers in implementing card-based systems, increasing success rates in this process. In addition, by reviewing recent production control systems, this dissertation aims to increase the repertoire of managers on existing systems, enabling the implementation of more appropriate options for the productive environment in which they are located.